Letter from Joseph Willicombe to Joseph Jelinek, July 1, 1938 - Joseph Willicombe::::::author::: (1938)
Office of William Randolph Hearst, Wyntoon, McCloud, California July 1, 1938 Dear Joseph: Thank you for the safe combinations which I received okey. We are all up here, and I wish you were with us. Except to be here only a short time, but return later on. Everybody that you know is well, including Gandhi and Helen and Jack Adams, also Mr. Kower, -- and I am feeling pretty good myself. The river is a wet as ever, and there is snow on Mount Shasta. The trees are full of leaves, -- and from all of this you will understand that things are just about the same way as when you were here before. I hope you are getting along okey. Please remember me to Julia, and looking forward to seeing you sometime in Los Angeles, believe me always, Your friend, J Willicombe